The Effect of Age Of Cassava Tapai (Manihot esculenta) and Concentration on The Characteristics of Cassava Tapai Flour - Selviani Selviani; Rima Azara (Universitas Muhammadiyah Sidoarjo, 2020)
The objective of this research was to find out the effects of age tapai and yeast concentration on characteristic of cassava tapai flour. This research was used Randomized Block Design (RAK) with two factors. The first factor was tapai that consist of three levels: 1 day, 2 days, 3 days and second factor was concentration of yeast 1%, 2%, and 3%. The result showed there was no interaction between tapai with concentration of yeast to all observated parameters, but had effect to colour hedonic. Tapai and concentration of yeast was effect on moisture, ash, density, and colour hedonic were affected positive. The best treatment was cassava tapai flour that was made using tapai 1 day and concentration of yeast 1% had moistured 6.53%; ash 2.45%; lightness 81.21; redness 6.72; yellowness 26.86; colour organoleptic 5.03; aroma 4.73; sugar reduction 0.85 mg/100ml; density 0,60 g/ml; and yield 20.12%